2006
DOI: 10.1007/s11547-006-0081-9
|View full text |Cite
|
Sign up to set email alerts
|

Grayscale calibration and quality assurance of diagnostic monitors in a PACS system

Abstract: Medical monitors turned out to be fully adequate to the task. Periodic QA tests are, however, absolutely necessary to ensure constant quality levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…It has been suggested that failure to keep the ideal technical conditions could be associated to the monitor lifetime [8]. An analysis of test results and age does not suggest a correlation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that failure to keep the ideal technical conditions could be associated to the monitor lifetime [8]. An analysis of test results and age does not suggest a correlation.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. 8, an 18 month follow-up of calibration and performance for 4 CRT and 10 LCD monitors (seven of them not manufactured for medical uses) was reported. The main results indicated gradual deterioration over time of the maximum luminance in the non-medical displays.…”
Section: Introductionmentioning
confidence: 99%
“…The formulation of such guidelines has been derived from a combination of expert consensus 11 and research demonstrating adverse degradation of image quality consequent to suboptimally performing displays. 3,[7][8][9][12][13][14][15][16] The Society of Motion Picture and Television Engineers (SMPTE) was one of the first organizations to develop guidelines from 1980 onwards and 'SMPTE RP 133-1991' 17 was the standard most commonly referred to in the assessment of medical display quality. In more recent times, an expert consensus subcommittee of the American Association of Physicists in Medicine (AAPM) and the National Electrical Manufacturers Association (NEMA) developed two comprehensive guidelines -The Assessment of Display Performance for Medical Imaging Systems 11 and the Digital Imaging and Communications in Medicine (DICOM) Part 14 Greyscale Standard Display Function standard 18 -commonly referred to as 'DICOM Part 14 GSDF'.…”
Section: Display Performance Standards Applicable To Diagnostic Medicmentioning
confidence: 99%
“…Recognition of the importance of displays in the practice of diagnostic medical radiology 3,8,[13][14][15]19 and the rapid growth of digital imaging in healthcare 13,20,21 has largely motivated the development of these comprehensive guidelines. Although these standards have not been legally mandated in any country (with the exception of Germany 22 ), much of the research in diagnostic medical radiology is fundamentally based on compliance with these standards.…”
Section: Display Performance Standards Applicable To Diagnostic Medicmentioning
confidence: 99%
“…A number of studies have found that, under the conditions considered, medical grade LCDs were comparable with CRT monitors and hard-copy radiograph films for diagnostic readings in radiology 2,3,11,12,14,17. However, the use of office-grade monitors for diagnosis has been discouraged, despite some studies that demonstrated acceptable quality 6,7.…”
Section: Introductionmentioning
confidence: 99%